Effect of transcrystallinity on the mechanical properties of glass fiber reinforced polypropylene composite - Lum, Dennis Li Ming. (2008)
The pupose of this study is to determine the effect that transcrystallinity has on the inerfacial properties and hence the mechanical properties of the glass-fribre reinforced polypropylene composite.